Cetakan visual sejarah pada era pemerintahan British di Sarawak berdasarkan koleksi Balai Seni visual Negara - Tahir, Azian; Mohd Noor, Arba’iyah; Mansor, Suffian (2014)
The visual record of Borneo between the 18th and 19th century appears to be the most important visual collections of our homeland. Whilst it is a collection of visuals both picturesque and romantic, there is significant historical information that can be derived as these visual details were obtained through merchants, travelers and professionals in this region during that period.These travelers and artisans hardly missed the point of recording visuals of their journey to Borneo as one of their stopover before proceeding to other popular destinations. These visual records are still available, carefully preserved and cataloged especially in Netherland, Portugal, England and our very own National Visual Art Gallery. In these papers, we will be able to focus on the visual collection at the National Visual Art Gallery of historical events during the time of British Colonial rule in Sarawak.In addition, this paper will also highlight the repertoire of visual record prints in various techniques produced through experience and sketches by travelers, tourists, government officials and their families who had been in Sarawak.During the same period, the British has also started documenting historical events taking place in Sarawak in sketches and thereafter by printing and reproducing the artworks in prints by publishing in booklets as well as portfolios.Besides that, the visuals will be analysed by examining local and foreign records for comparison.These documentations will assist the completion of historical research not only through records but also through exploration of historical events, travels/journeys made by colonials in visual form.